Repurposing Historic Drugs for Neutrophil-Mediated Inflammation in Skin Disorders - Ludovica Franceschin; Alessia Guidotti; Roberto Mazzetto; Jacopo Tartaglia; Christian Ciolfi; Mauro Alaibac; Alvise Sernicola (Biomolecules)
Neutrophil-mediated inflammation is a key feature of immune-mediated chronic skin disorders, but the mechanistic understanding of neutrophil involvement in these conditions remains incomplete. Dapsone, colchicine, and tetracyclines are established drugs within the dermatologist’s therapeutic armamentarium that are credited with potent anti-neutrophilic effects. Anti-neutrophilic drugs have established themselves as versatile agents in the treatment of a wide range of dermatological conditions. Some of these agents are approved for the management of specific dermatologic conditions, but most of their current uses are off-label and only supported by isolated reports or case series. Their anti-inflammatory and immunomodulatory properties make them particularly valuable in managing auto-immune bullous diseases, neutrophilic dermatoses, eosinophilic dermatoses, interface dermatitis, and granulomatous diseases that are the focus of this review. By inhibiting inflammatory pathways, reducing cytokine production, and modulating immune responses, they contribute significantly to the treatment and management of these complex skin conditions. Their use continues to evolve as our understanding of these diseases deepens, and they remain a cornerstone of dermatological therapy.